PREPARATION OF BAMBOO DISSOLVING PULP FOR TEXTILE PRODUCTION; PART 1. STUDY ON PREHYDROLYSIS OF GREEN BAMBOO FOR PRODUCING DISSOLVING PULP - Xiaojuan Ma; LiuLian Huang; Yanxi Chen; Lihui Chen (BioResources, 2011)
Prehydrolysis was used as the first treatment of bamboo materials for producing high dissolving pulp for textile applications. In this paper, green bamboo (Dendrocalamopsis oldhami) was hydrolyzed in water, and the hydrolysis process was optimized. The morphology and super-molecular structures of the raw material and prehydrolyzed material were studied by SEM and XRD, respectively. Based on the optimum conditions, a study of the kinetics and mechanism showed that pentosan dissolution during the hydrolysis process was a first order reaction. When cooking temperature was 150 oC, 160 oC, 170 oC, and 180 oC, the corresponding reaction rate constants were 0.00411h-1, 0.00495h-1, 0.00730h-1, and 0.00925h-1, respectively. The activation energy was 44.94 kJ/mol based on the Arrhenius empirical equation. SEM results revealed that after the pre-hydrolysis process, the bamboo structure became loose because of hemicellulose dissolution, which created a favorable environment for chemical penetration in the subsequent treatment. Furthermore, the degree of crystallinity was increased from 45.43% to 57.06% during the prehydrolysis. Both the treated and the untreated fibers were assumed to be cellulose I.